Better left unsent : [large type] a novel - Louis, Lia (Center Point Large Print, 2025)
"Two years ago, thirty-year-old receptionist Millie Chandler had her heart spectacularly broken in public. Ever since, she has been a closed book, vowing to keep everything to herself her feelings, her truths, even her dreams in an effort to protect herself from getting hurt again. But Millie does write emails -- sarcastic replies to her rude boss, hard truths to her friends, and of course, that one-thousand-word love declaration to her ex who is now engaged to someone else. The emails live safely in her drafts, but after a server outage at work, Millie wakes up to discover that all her emails have been sent. Every. Single. One. As every truth, lie, and secret she's worked so hard to keep only to herself are catapulted out into the open, Millie must fix the chaos her words have caused, and face everything she's ever swept under the carpet."--